2009
DOI: 10.1093/petrology/egn071
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Ni-Co-O-S Phase Relations in Peridotite-Seawater Interactions

Abstract: Serpentinization of abyssal peridotites is known to produce extremely reducing conditions as a result of dihydrogen (H 2 ,aq) release upon oxidation of ferrous iron in primary phases to ferric iron in secondary minerals by H 2 O. We have compiled and evaluated thermodynamic data for Fe^Ni^Co^O^S phases and computed phase relations in fO 2 ,g^fS 2 ,g and aH 2 ,aq^aH 2 S,aq diagrams for temperatures between 150 and 4008C at 50 MPa. We use the relations and compositions of Fe^Ni^Co^O^S phases to trace changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
171
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(186 citation statements)
references
References 80 publications
(117 reference statements)
10
171
0
5
Order By: Relevance
“…These experiments were performed using methods very similar to those of this study, except that the reaction vessel was periodically rotated during heating. After heating for [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] (Table 1). However, isotopic labeling indicated that the CH 4 in our experiments was not derived from reduction of dissolved inorganic carbon but instead, was derived entirely from background sources (i.e., composed of 99 mol % 12 CH 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments were performed using methods very similar to those of this study, except that the reaction vessel was periodically rotated during heating. After heating for [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] (Table 1). However, isotopic labeling indicated that the CH 4 in our experiments was not derived from reduction of dissolved inorganic carbon but instead, was derived entirely from background sources (i.e., composed of 99 mol % 12 CH 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…This situation might arise, for instance, at the serpentinization reaction front, where localized consumption of H 2 O and production of H 2 (Reaction 1) can lead to saturation of the fluid and exsolution of H 2 -rich vapor bubbles. Indeed, the relatively common occurrence of the NiFe alloy awaruite in many serpentinites may be an indication that such conditions may be widespread, because formation of this mineral requires highly elevated H 2 concentrations that may approach saturation levels (32,35). Because NiFe alloys can also catalyze the reduction of inorganic carbon to CH 4 (16), it may make these environments even more favorable for CH 4 synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…These reactions indicate the coexistence of magnetite with highly reduced gas phases (cf., Klein and Bach, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In general, dihydrogen (H 2,aq ) is released during hydrothermal alteration/serpentinization of ultramafic rocks due to the oxidation of Fe 2+ in primary silicates (via addition of water), producing Fe 3+ in secondary minerals (e.g. magnetite commonly forms during serpentinization) 15 . A high degree of serpentization would thus evolve a significant amount of H 2,aq , and metamorphic conditions would become reducing.…”
mentioning
confidence: 99%
“…This desulphurization process is triggered by the release of H 2,aq during serpentinization. At higher oxygen and sulphur fugacities that may occur due to more intense serpentinization/steatization, awaruite breaks down to millerite and magnetite instead 15 . Experimental study shows that the development of pentlandite + awaruite + magnetite assemblages imply hydrogen concentrations close to (or at) the solubility of dihydrogen in water: between 200C and 300C (ref.…”
mentioning
confidence: 99%